Communication strategies in a value-related crisis - Steinwall, Alexandra (2021)
The global food system faces great challenges in terms of sustainability. The access to food is unevenly distributed and one third of the population is either suffering from micro deficiencies or from a high calorie intake. Moreover, the food productions system contributes to more than 25 % of the total greenhouse gases and 18 % of these stems from livestock. With a growing population demanding more of these climate intense products, great challenges await. Subsequently, a change of diets to one including more plant-based products is seen as one solution to substantially reduce negative impacts of consumption and reach a more sustainable planet. Stakeholders are expecting corporations to act responsible and incorporate CSR into their business conducts. This is especially true for corporations in the food system when facing challenges that can eventually escalate to a crisis. The aim of this study was to examine how a corporation communicate to its consumers in a value-related crisis. This encompasses finding out what communication strategy is used and the reputational outcome from this approach. The study was constructed as a case study of the communication of a Swedish oat milk company. How the corporation communicated was examined from their main communication channels: sustainability reports, webpage, and social media. Moreover, three focus groups were conducted with the corporation’s consumers and a corporate representative to gain a deeper understanding of the study phenomenon. Based on corporate social responsibility, corporate social responsibility communication, situational crisis communication theory and social media, a theoretical framework was created to guide the analysis of data. Findings of the study show that the corporation used a denial- and a CSR communication strategy. It is suggested by the theoretical framework that these strategies were not sufficient nor successful in this endeavour of protecting the reputation in a crisis. In crisis communication through social media, it is perceived important with strategies that are more accommodating to consumer expectations to protect corporate reputation. The corporation’s prior reputation and CSR actions was expected to shield a corporation in a crisis which was not perceived to be the case for the studied corporation. Neither did the response strategy protect the reputation as this was not found fitting for the specific crisis situation. Though, it was found that the financials were not affected, and the corporation continued to grow in a rapid phase. Therefore, it is suggested that the reputation was only slightly affected, if affected at all, in the end.